Effectiveness of a program for early detection/intervention in children/adolescents with generalized social phobia - Sánchez-García, Raquel; Olivares, José (Anales de Psicología / Annals of Psychology, 2009)
The aim of this paper is to study the effects of the psychological treatment Intervención en Adolescentes con Fobia Social / Intervention in Adoles-cents with Social Phobia (IAFS / IASP; Olivares, 2005) in the version for 10-14 year olds, analysing its effects without the cognitive restructuring com-ponent. The sample is composed of 82 children and adolescents (73% female; 27% male) with generalized social phobia and a mean age of 11.91 years (SD = 1.33; range: 10-14 years). Participants were randomly assigned to three experimental conditions: 25 to the wait list control group, 28 to the complete IAFS condition and 29 to the IAFS without cognitive restructuring condition. The results show significant changes (improvement) in all the de-pendent variables evaluated in the two treatment conditions.